Risk Factors Dental Caries Based on Disease Indicator CAMBRA in Preschool Children - Quroti Ayun; Wiworo Haryani; Dewi Risnawati (Jurnal Kesehatan Gigi, 2026)
The prevalence of dental caries in preschool-aged children is relatively high, and it can impact their growth, development, and quality of life. It is necessary to reduce the risk of caries by assessing and managing its risk factors. One effective method is CAMBRA ( Caries Management by Risk Assessment) that can reduce the risk of dental caries. This study aims to obtain risk factors dental caries based on CAMBRA in preschool children. This study was an observational cross-sectional study with a sample of 57 preschool children in ABA Niten Kindergarten in the Yogyakarta. A total sampling method was used, the dependent variable was the number of caries and the independent variable were adopted from CAMBRA, namely: white spots, dental fillings, dental plaque/gingival inflammation, low salivary flow, salivary pH, and deep fissures. Data were collected using a checklist and analyzed using the Chi-Square test. The result were 46 children (80,7%) had dental caries, 41 children (71.93%) had teeth with white spots, 32 (56.14%) had no dental plaque, 34 (59.63%) had low salivary flow, 40 (70.18%) had a low salivary pH , 42 (73.68%) had no dental fillings, and 30 (52.63%) had deep fissures. The Chi-square analysis revealed that white spots, dental fillings, dental plaque, low salivary flow, salivary pH, and deep fissures were significantly associated with the dental caries (p<0.05). white spots, dental fillings, dental plaque, low salivary flow, salivary pH, and deep fissures are related to the occurrence of dental caries.